The past as a digital playground : archaeology, virtual reality and video games - Bertoldi, Stefano,; Mariotti, Samanta, (Archaeopress Publishing Ltd, 2022)
This book collects the contributions to a two-day conference which illustrate a digital project developed at the Archaeological and Technological Park of Poggibonsi (Siena, Tuscany), where Virtual Reality and an educational video game are being used to enhance the archaeological content deriving from the excavation of the medieval site.